Transformasi Kebijakan Anti-Bullying di Sekolah Dasar - Azhary, Luqman; Handoyo, Eko; Waluyo, Edi (Joyful Learning Journal, 2025)
This article discusses the transformation of anti-bullying policies in elementary schools, focusing on the development of implementation and the impact of these policies on the learning environment. This study was conducted at SD Negeri 1 Mangunharjo, Tembalang, Semarang City. The study used a qualitative approach. The researchers conducted surveys and interviews with students, teachers, and parents to assess their understanding of the existing anti-bullying policies. The findings of the study indicate that although the policies have been introduced, there is still a gap between the written policies and actual implementation. Many teachers and school staff do not receive adequate training to handle bullying cases effectively. Students are often unaware of the policies and do not feel comfortable reporting them. In addition, this study found that a positive and inclusive school environment is important in reducing bullying rates. Through an analysis of the policies and practices implemented, this article suggests important steps that need to be taken to improve anti-bullying policies, including the need for teacher training, parental involvement, and strengthening the role of students in creating a culture of respect for differences. It is hoped that the findings of this study can provide references for policy makers and educators to create a safe and friendly school environment for all students.